55/5ab + 4/5ab = 59/5ab
7ab-5ab = 2
gcd of 5ab,28xy
(5ab)2 = 25a2b2 (provided a and b are elements of a commutative group).
The GCF of 5ab and 56b squared is b.
(5ab^2 + 4cd)(5ab^2 4cd) <
6a2 + 5ab - 6b2 = (3a - 2b)(2a + 3b)
No. 2a is one thing, 3b is another. If you add them together, they become 2a + 3b. 5ab indicates that multiplication has taken place. 5 times a times b = 5ab
5ab(3a - 2b)
5ab-2ab+4a-b+5b = 3ab+4a+4b
3a2b is the simplest formImproved Answer:-3a x 2b = 6ab when simplified
Considering the minus sign between 5ab and 6b2 then we have the polynomial as 6a2 + 5ab - 6b2. The polynomial is a quadratic polynomial.Steps to factorize a quadratic polynomial:1 - Multiply first term by third term. 6a2 x (-6b2) = -36a2b22 - If possible break the second term into two terms such that they multiple to -36a2b2. If not then it is factorized by Sridharacharya's formula.5ab can be broken as 9ab + (-4ab).These two terms multiply to give -36a2b2.So we can write 6a2 + 5ab - 6b2 = 6a2 + 9ab + (-4ab) - 6b2.6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)(3a - 2b).So the factors are (2a + 3b) and (3a - 2b).
8(8 - 5ab)
6a2 + 5ab - 6b2 = 6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)*(3a - 2b)
What is The simplified form of (3a2 - 5ab plus c2) plus (-2a2 plus 10ab plus 6c2)
(3a - 2b)(2a + 3b)
They are 4 terms of an algebraic expression.